Manuscripts and translations: Spaces for creation - Romanelli, Sergio (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Abstract: In this article I present my research on genetic criticism applied to translation carried out in the past ten years – partly during my doctoral studies and now in my post-doctoral internship in Belgium. In both cases, I associate the methodology of Genetic Criticism, with the focus on artistic creation, to the documentation regarding the process of translations: in the former case, I examined the translation process of Emily Dickinson´s poems into Italian by the poet and translator Rina Sara Virgillito; in the second case, I looked into the process of translation from various classic and modern languages into Portuguese, by the Emperor of Brazil, Dom Pedro II. The objective of both studies was to establish, within the new paradigm of systemic thinking, a true transdisciplinarity between the genesis of texts (text genetics) and translation studies, so that the former may assist in the creative process of the translator – here understood as a true authoring process -, and the latter may provide speculative tools for a transversal methodology in search of a theory of its own. Finally, I consider both the manuscripts and the translational activity as spaces for creation, of effective new signification of signs due to their unstable nature.